A quantitative analysis of stratospheric HCl, HNO3, and O3 in the tropopause region near the subtropical jet. Issue 9 (14th May 2014) - Jurkat, T.; Voigt, C.; Kaufmann, S.; Zahn, A.; Sprenger, M.; Hoor, P.; Bozem, H.; Müller, S.; Dörnbrack, A.; Schlager, H.; Bönisch, H.; Engel, A.
<x xml:space="preserve">Abstract</x> The effects of chemical two‐way mixing on the Extratropical Transition Layer (ExTL) near the subtropical jet are investigated by stratospheric tracer‐tracer correlations. To this end, in situ measurements were performed west of Africa (25–32°N) during the Transport and Composition of the Upper Troposphere Lower Stratosphere (UTLS)/Earth System Model Validation (TACTS/ESMVal) mission in August/September 2012. The Atmospheric chemical Ionization Mass Spectrometer sampling HCl and HNO3 was for the first time deployed on the new German High Altitude and Long range research aircraft (HALO). Measurements of O3, CO, European Centre for Medium‐Range Weather Forecasts (ECMWF) analysis, and the tight correlation of the unambiguous tracer HCl to O3 and HNO3 in the lower stratosphere were used to quantify the stratospheric content of these species in the ExTL. With increasing distance from the tropopause, the stratospheric content increased from 10% to 100% with differing profiles for HNO3 and O3. Tropospheric fractions of 20% HNO3 and 40% O3 were detected up to a distance of 30 K above the tropopause.